Synthesis and characterization of cellulose reinforced chitosan hydrogel as potential bioink for 3D printed articular cartilage scaffolds - Quindoza, Gerardo Martin D. III
Fabrication via 3D printing for tissue engineering applications is becoming prominent nowadays. This allows the construction of patient-specific and cost-effective tissue scaffolds with easiness. These scaffolds are implanted to a target area, such as a damaged knee articular cartilage, to allow regeneration of the native tissue and repair of its defects. What remains a big hurdle is the selection of the proper ink material or bioink for the printer. Chitosan is an established material that may be utilized for tissue scaffolds and it has the viscoelastic properties that makes it printable; however, it still has limitations in its properties. This study aims to synthesize a chitosan hydrogel reinforced with cellulose to address the limitations. It also assessed the potential of the resulting composite hydrogel as articular cartilage bioink. The hydrogels were synthesized via thermoresponsive sol-gel method and were characterized using Fourier transform infrared (FTIR) spectroscopy, swelling studies, in-vitro biodegradation, and rheological measurements. FTIR spectra showed that the synthesized hydrogels contain a semi-interpenetrating network of polymers, with interactions primarily due to physical crosslinking. Furthermore, it was established that the addition of cellulose has resulted to significant changes in hydrogel properties. The swelling of the hydrogel increased with addition of cellulose while the degradation rate slows down. Results of rheological tests have shown that the material exhibits shear thinning and behaves more gel-like than liquid making it printable. However, high cellulose amounts caused clogging while printing, and presence of water affects the continuity of extruded layers. The results of this study have shown the potential of a composite cellulose-chitosan hydrogel to serve as bioink specifically for 3D printing of articular cartilage.